การปรับปรุงคุณภาพแรงดันของเครื่องกำเนิดไฟฟ้าเหนี่ยวนำ แบบกระตุ้นตัวเองด้วยวงจรกรองแอกทีฟ - ประจวบ เอี่ยมสำอาง (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Squirrel-cage induction generators are more suitable for renewable energy system than synchronous generators because of their low costs, robustness and less maintenance requirements. The induction machine can be operated as an induction generator by connecting external capacitors across its stator terminals and using the residual flux in the rotor core to build up the voltage. The steady-state output voltage depends on the rotor speed, the load and the capacitor value. However, in practice, it is found that the induction generator exhibits a large voltage drop when feeding inductive loads, and produces voltage distortion and imbalance when feeding nonlinear and unbalanced loads. To overcome these problems, this thesis presents an improvement of voltage quality of a self-excited induction generator using an active filter connected in parallel with a capacitor. The function of the active filter is to detect and compensate harmonics, current imbalance, and reactive power caused by loads so as to restore a balanced and undistorted output voltage of constant amplitude. Experimental results are given to confirm the effectiveness of the proposed techniques.